THE PROBLEMS TEACHERS EXPERIENCE IN PERFORMING THEIR TASKS - TAYHAN, Hasan; GÜNDÜZ, Yüksel (Atlas Journal, 2022)
The purpose of this research is to show what problems teachers have experienced in the process of performing their tasks. The study group of this research, a qualitative study, consists of 29 teachers in primary schools and secondary schools in Samsun İli Salıpazarı District National Education Directorate in 2019-2020 academic year. The data of the research is determined by the sample method. The research uses a semi-structured interview form as a data collection tool. Qualitative data analysis methods (descriptive and content) were used in the analysis of the data obtained from the conversation. The study asked questions about teachers, management, teachers, parents, students and the environment. When the research results were examined, many of the teachers said that the problems arising from managers were in the first place that managers had unjust attitude and behavior among teachers. The second biggest problem is that the language and attitude that managers use to communicate with teachers is harsh and rude. The problem with their colleagues was that teachers were not sharing and they were self-centered, and the second problem was that some teachers were trying to displace their responsibilities and put their responsibilities on their zumers. It was stated that the parents and students were not responsible for their problems with parents and students at the beginning. The second problem in favor of the student was the disrespectful attitude and behavior that the parent and the student demonstrated against the teacher. The overall reputation of environmental problems and the low societal structure around the school is expressed as low socio-economic structure and poor physical conditions of the school, small classrooms, lack of school gardens and playgrounds, lack of laboratory and gym, music, painting and workshops.